Application of silver nanodendrites deposited on silicon in SERS technique for the trace analysis of paraquat. (15th February 2016) - Dao, Tran Cao; Luong, Truc Quynh Ngan; Cao, Tuan Anh; Kieu, Ngoc Minh; Le, Van Vu
Abstract: In order to detect trace concentrations of organic or biological molecules by surface-enhanced Raman scattering (SERS) technique, the SERS-active substrates with high enhancement factor are required. The silver nanodendrites (AgNDs) are a growing class of such SERS-active substrates. This report presents the preliminary results of the trace detection of paraquat (PQ), a commonly used herbicide, with the use of SERS-active substrates, which have been made from AgNDs deposited on silicon. The AgNDs were produced either by electroless deposition, or by electrodeposition onto a silicon wafer, using aqueous solution of HF and AgNO3 . It was observed that the silver dendrites are formed only when AgNO3 concentration is high enough. Next, it was found that with the additional assistance of an electric potential in the electrodeposition, the dendrites have grown up with the more perfect ramification. The AgNDs with more perfect branching gave the Raman spectrum of PQ with higher enhancement factor. More specifically, while the SERS-active substrates prepared from electrodeposited AgNDs were able to detect PQ with concentration as low as 0.01 ppm, the ones made from electroless deposited AgNDs could only detect PQ at concentration of hundreds times higher.